2014
DOI: 10.1007/s11934-014-0448-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Bladder: from Diagnosis to Management

Abstract: Patients with spinal cord injury (SCI) present with a wide range and variety of urologic manifestations, depending upon the level of injury. Historically, patients with spinal cord injury experienced significant mortality related to renal failure. Greater knowledge of the pathophysiology of SCI, however, has contributed to a reduction in mortality. It is essential to perform a thorough initial evaluation and regular follow-up of these patients to achieve the primary goal of preservation of renal function, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 76 publications
2
21
0
1
Order By: Relevance
“…Neurogenic bladder dysfunction due to spinal cord injury (SCI) includes detrusor overactivity (DO) and low bladder compliance. In clinical practice, these functional abnormalities can induce bladder deformity, reduction of bladder capacity, hydronephrosis and vesicoureteral reflux (VUR), potentially resulting in renal dysfunction, and a decline in quality of life (QoL) along with the progression of urinary incontinence . Therefore, the major aim of treatment for neurogenic bladder dysfunction is to manage DO and low bladder compliance properly, thereby keeping the normal renal function and improving the QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Neurogenic bladder dysfunction due to spinal cord injury (SCI) includes detrusor overactivity (DO) and low bladder compliance. In clinical practice, these functional abnormalities can induce bladder deformity, reduction of bladder capacity, hydronephrosis and vesicoureteral reflux (VUR), potentially resulting in renal dysfunction, and a decline in quality of life (QoL) along with the progression of urinary incontinence . Therefore, the major aim of treatment for neurogenic bladder dysfunction is to manage DO and low bladder compliance properly, thereby keeping the normal renal function and improving the QoL.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, little has been published on the rate of urologic reconstruction/urinary diversion among SCI patients; most of the literature consists of mixed case series from expert centers. 9,22 In general, urinary incontinence is common among SCI patients 23 ; however, we found that the utilization of urologic reconstruction/urinary diversion surgeries (including stress incontinence procedures) is low. With further follow-up, progressive neurogenic bladder dysfunction, and failure of more conservative treatment options, the use of these procedures may increase.…”
Section: Discussionmentioning
confidence: 85%
“…34 Neurogenic bladder dysfunction with varying degrees of detrusor hypo/hyper or areflexia and sphincter tone deficiencies causing incontinence can be treated with clean intermittent catheterization (CIC), indwelling catheter (urethral or suprapubic) placement and onabotulinumtoxinA injections. 35 Similarly, bladder outlet obstruction (BOO) typically leads to urinary retention but can present as overflow incontinence in males and is primarily managed with an indwelling catheter and/or prostate reduction surgeries. 36 While transurethral bulking agents have been described as a viable option for urinary incontinence, results are mixed and short-lived, if any.…”
Section: Discussionmentioning
confidence: 99%